The Failure of Internal Audit in Detecting Corporate Fraud Through Global Cases Study - Fitri Setiabudi (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
This study investigates the reasons internal audit functions frequently fail to detect corporate fraud by examining fifteen global fraud cases through qualitative content analysis. It draws on a range of secondary materials, including academic literature, regulatory reports, investigative documents, and publications from the Association of Certified Fraud Examiners, to identify patterns that consistently emerge across cases. The results reveal enduring weaknesses such as limited independence, excessive reliance on management information, inadequate fraud risk assessment, insufficient professional skepticism, and the use of outdated audit techniques. These patterns are interpreted using the Fraud Triangle, Agency Theory, and the COSO Internal Control Framework to explain the systemic nature of internal audit failure. The findings suggest that internal audit ineffectiveness stems primarily from structural, cultural, and governance-related constraints rather than from procedural deficiencies alone. Overall, the study offers a cross-case synthesis that integrates multiple theoretical perspectives and provides practical insights for strengthening internal audit practices and enhancing fraud detection within corporate organizations